Analysis of Deficits in Total Knee Replacement Cases at Siti Fatimah Hospital, South Sumatera - Ramadhan Ananditia Putra; Ian Ervan Simanungkalit; Muhammad Ilham Satya Nugraha (Jurnal Manajemen Kesehatan Indonesia, 2023)
Health is one of the basic human needs and is a right for every citizen that is protected by law. The form of the State's efforts in providing health services is by launching the National Health Insurance Program (JKN) through the Social Security Administration Agency. In practice, many cases experience a deficit related to costs incurred by the Hospital and costs obtained through INA-CBG's claims. The purpose of this study was to see if there were any adverse differences in the Total Knee Replacement case carried out at Siti Fatimah Hospital. This research was quantitative, descriptive research in hospital. Data collection was a total of 19 patients suffering from knee Osteoarthritis and who had to do Total Knee Replacement at Siti Fatimah Hospital from 2020-2023. The results of the study found that in every case of Total Knee Replacement the hospital always experienced a deficit. In average national healthcare system only reimbursed half of our cost. Further evaluation of INA-CBGs reimbursement scheme is necessary to ensure hospital to achieve ideal cost recovery when patients are treated.